“Like, Subscribe, and Share”: Students' Views on Using YouTube Videos to Improve Their English Vocabulary - Ahmad Harris Setyonyoto (Fakultas Ilmu Budaya, Universitas Brawijaya, 2022)
In the effort of learning speaking at school, oftentimes students should face difficulty to master the skill. Many EFL students struggle to speak in English because they have insufficient vocabulary to express their opinion. Hence, improving vocabulary has become one of the many focuses for teachers in teaching English. Oftentimes, teachers use YouTube as a media to improve students’ vocabulary. This paper aims to investigate and describe deeper insights on students’ perspective on using YouTube videos to improve vocabulary in speaking English. Employing a descriptive qualitative method, an open-ended questionnaire administered to 103 senior high school students. The result of the study showed that the majority of the students admitted that they have a positive perspective in using YouTube as a media to improve their vocabulary. Nevertheless, some students also prefer to learn vocabulary from the teachers in the usual classroom settings.